(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Aship on the high seas,as ageneral rule, while in it,is not subject to the state to which it belongs by its nationality,and this is know as the principle of the Of the flag state. The international community needs solidarity to fight it.these internationally prohibitied activites are represented in maritime piracy,salve trade,illict drug trafficking the crime of illegal radio broadcasting. From this point of view, international law initiated the establishment of controls to ensure the exercise of these freedoms within alegal authority and global jurisdiction incombating this serious crime,wich they have the right to pursue on the highseas.